Beta cell specific probing with fluorescent exendin-4 is progressively reduced in type 2 diabetic mouse models. Issue 6 (19th February 2016) - Lehtonen, Janne; Schäffer, Lauge; Rasch, Morten Grønbech; Hecksher-Sørensen, Jacob; Ahnfelt-Rønne, Jonas
Abstract : Probes based on GLP-1R agonist exendin-4 have shown promise as in vivo β cell tracers. However, questions remain regarding the β cell specificity of exendin-4 probes, and it is unclear if the expression levels of the GLP-1R are affected in a type 2 diabetic state. Using in vivo probing followed by ex vivo imaging we found fluorescent exendin-4 probes to distinctly label the pancreatic islets in mice in a Glp-1r dependent manner. Furthermore, a co-localization study revealed a near 100 percent β cell specificity with less than one percent probing in other analyzed cell types. We then tested if probing was affected in models of type 2 diabetes using the Lepr db/db (db/db) and the Diet-Induced Obese (DIO) mouse. Although nearly all β cells continued to be probed, we observed a progressive decline in probing intensity in both models with the most dramatic reduction seen in db/db mice. This was paralleled by a progressive decrease in Glp-1r protein expression levels. These data confirm β cell specificity for exendin-4 based probes in mice. Furthermore, they also suggest that GLP-1R targeting probes may provide a tool to monitor β cell function rather than mass in type 2 diabetic mouse models.